Use of My Health Record by Clinicians in the Emergency Department: An Analysis of Log Data - Mullins, Alexandra K.; Morris, Heather; Enticott, Joanne; Ben-Meir, Michael; Rankin, David; Mantripragada, Kumar; Skouteris, Helen (Frontiers in Digital Health, 2021)
Objective: Leverage log data to explore access to Australia’s national electronic health record, My Health Record, in the emergency department - by clinicians. Materials and methods: A retrospective analysis was conducted using secondary routinely collected data. Log data regarding all patients who presented to the emergency department between 2019-2021 of a not-for-profit hospital (that annually observes 23,000 emergency department presentations) were include in this research. Attendance data and human resources data were linked with My Health Record log data. The primary outcome was a dichotomous variable indicating if a patients’ My Health Record was accessed. Logistic regression facilitated the exploration of factors (user role, day of the week and month) associated with access. Results: My Health Record was accessed by a pharmacist, doctor or nurse in 19.60% (n=9,262) of all emergency department presentations. Access was dominated by pharmacists (18.31%, n=8,656). All users demonstrated a small, yet significant, increase in access with each one month increase in time (odds ratio = 1.07, 95%, confidence Interval: 1.06-1.07, p = < 0.001). Discussion: Doctors, pharmacists and nurses are increasingly accessing My Health Record – yet pharmacists are accessing My Health Record substantially more than other user groups in this research. However, access to My Health Record occurs for only one in every five patients who present to the emergency department, indicating a need remains to accelerate and encourage MHR adoption and access by clinicians.